THE DIRECTED INQUIRY ACTIVITY MODEL TO IMPROVE STUDENT LEARNING OUTCOMES MATERIAL BIOGRAPHICAL TEXT IN CLASS XI IPS 2 SMA NEGERI 1 GEDEG MOJOKERTO - Endang Sri Catur Pratiwi (Sean Institute, 2022)
Based on the initial analysis, it can be seen that out of the 6 classes taught by the researcher, there were 4 classes in the low category, one of which was class XI IPS 2. The general condition of this class was generally heterogeneous with the majority of academic abilities being at the lower middle level. The results of the repetition are very low, namely the completeness of the daily repetition of the previous material is only below 60%. In addition, the enthusiasm of students in participating in learning activities is also low, this is indicated by the number of students who seem indifferent to Indonesian language lessons, often joke and even chat privately with friends. Another finding in class XI IPS 2, namely the lack of students who dare to answer questions or are willing to ask voluntarily, students generally have to be forced to ask or answer questions . Based on this, efforts to improve learning are needed, one of which is by applying the Directed Inquiry Activity model. This type of research is classroom action research, which aims to determine the increase in student learning outcomes by using the Directed Inquiry Activity Model in biographical texts. in SMA Negeri 1 Gedeg Mojokerto Class XI IPS 2 Semester 2. This research was conducted in class XI IPS 2 SMA Negeri 1 Gedeg involving 3 2 students and researchers assisted by 2 observers. The results showed that learning using the Directed Inquiry Activity model could improve student learning outcomes. In addition, learning using the Directed Inquiry Activity model in biographical texts SMA Negeri 1 Gedeg class XI IPS 2 semester 2 2019/2020 school year run more effectively which is marked by increased student enthusiasm . In addition, the Directed Inquiry Activity model can also improve the quality of learning, this is evidenced by the increase in the average score of learning implementation.